Nonalcoholic or metabolic-associated fatty liver disease and colorectal polyps: evidence from meta-analysis and two-sample Mendelian randomization - Zhai, Dong; Xu, Sumei; Liu, Haoge; Tong, Xiaojuan (Frontiers in Genetics, 2024)
Introduction: Nonalcoholic or metabolism-associated fatty liver disease (NAFLD or MAFLD) and colorectal polyps are chronic conditions strongly linked to lifestyle factors. However, the precise causal link between NAFLD or MAFLD and the development of colorectal polyps is not yet fully understood. This study aimed to evaluate the association between NAFLD or MAFLD and the risk of colorectal polyps based on a meta-analysis and two-sample Mendelian randomization (MR) analyses. Methods: PubMed, Embase, Cochrane Library databases were searched for eligible studies to be included in the meta-analysis We conducted a thorough search of the PubMed, Embase, and Cochrane Library databases to identify eligible studies prior to March 22, 2024. Subgroup analyses were performed based on sex, age, and geographical region. Causality between NAFLD/MAFLD and colorectal polyps was explored by using two-sample Mendelian randomization (MR) analyses. Results: Based on an analysis of 17 studies encompassed within this meta-analysis, a significant correlation was identified between the presence of NAFLD/MAFLD and elevated incidence of colorectal polyps (NAFLD: OR = 1.57, 95% CI: 1.43-1.73, I 2 = 38%, p =0.06; MAFLD: OR=1.67, 95% CI: 1.40-2.00, I 2 = 77%, p =0.002). However, the current body of evidence does not support a causal relationship between NAFLD/MAFLD and the prevalence of colorectal polyps (OR = 0.9998315, 95% CI: 0.9987566-1.000907, P = 0.7587638). Conclusion: NAFLD/MAFLD demonstrated a significant positive correlation with an elevated risk of developing colorectal polyps. However, the MR analysis suggested that no causal relationship existed between NAFLD/MAFLD and colorectal polyps. Therefore, further research is required to identify the underlying mechanism of causal link between these diseases.